Myxoma - Silva de Villar, Gladys (Cirugía del Uruguay, 1973)
Myxomas are rare tumors of soft parts with histological characteristics similar to that of primitive mesenchyme or embryonic mucuous tissue. They are local!y malignant but never produce metastasis; however if abscission is conservative they may recur. Myxomas, which are real neoplasias, should not be mistaken with mucoid degeneration areas of other tumors of conjuntive origin.